2011
DOI: 10.1007/s13361-011-0251-4
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Electrospray Ionization Emitters with Differing Geometries with Respect to Flow Rate and Electrospray Voltage

Abstract: The performance of several electrospray ionization emitters with different orifice inside diameters (i.d.s), geometries, and materials are compared. The sample solution is delivered by pressure driven flow, and the electrospray ionization voltage and flow rate are varied systematically for each emitter investigated, while the signal intensity of a standard is measured. The emitters investigated include a series of emitters with a tapered outside diameters (o.d.) and unaltered i.d.s, a series of emitters with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…The response appears to be flow rate sensitive at low flow rates (30–200 nL/min) and concentration sensitive at high flow rates (>200 nL/min). A similar trend was reported using a fused silica emitter with a 50 μm id and an etched od . In the flow rate sensitive region, ionization efficiency improved at very low flow rates .…”
Section: Resultssupporting
confidence: 80%
“…The response appears to be flow rate sensitive at low flow rates (30–200 nL/min) and concentration sensitive at high flow rates (>200 nL/min). A similar trend was reported using a fused silica emitter with a 50 μm id and an etched od . In the flow rate sensitive region, ionization efficiency improved at very low flow rates .…”
Section: Resultssupporting
confidence: 80%
“…Low flow rates have been reported to increase ion intensity [61]. The flow rate in our ESI experiments was ~2.5 μL/min, while the nanoESI flow rate was ~0.2 μL/min.…”
Section: Resultsmentioning
confidence: 97%
“…Herein, despite using a smaller particle stationary phase (3.5 µm particle size) and acetonitrile as an eluent, the chromatogram performance improved; the findings suggest that the gradient eluent plays a key role in the efficiency of gallic acid detection and the enhanced content of gallic acid. Studies have shown the influence of gradient elution using increased acetonitrile and flow rate modification [56,57]. Increasing flow rate can lead to faster elution of analytes, whereas decreasing flow rate results in better resolution and improved concentration-sensitive detection.…”
Section: Hplc Methods Validationmentioning
confidence: 99%